Isolation, identification and efficacy assessment of bacteria degrading azo dye & reactive dye from river sludge sample - Purkaystha, Anirban; Megha, Sumiya Al Sadia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2022.